Academies in Health Professions Education: A Scoping Review. (11th May 2021) - Uijtdehaage, Sebastian; Ho, Ming-Jung; Harvey, Emily; Dorris, C. Scott; Huggett, Kathryn N.
Abstract : Supplemental Digital Content is available in the text. Abstract : Purpose: Thirty years ago, academies were conceived as a sociocultural approach to revitalize the teaching mission of medical schools and to promote educators' career advancement. The academy movement has grown rapidly and now reaches a broad range of health professions education organizations. The authors conducted a scoping review to map the literature and describe the evidence that guides the formation of new academies and justifies the continuation of existing ones. Method: The authors searched MEDLINE (via Ovid), Embase (via Elsevier and Ovid), CINAHL (via EBSCOhost), and Web of Science (via Clarivate Analytics) from inception through March 6, 2020, for publications regarding academy-like organizations. They mapped the relevant literature using logic modeling as an organizing framework and included the mission, resources, activities, output, outcomes, and impact of the included academies. Results: Of the 513 publications identified, 43 met the inclusion criteria, the oldest of which was published in 2000. Most publications were either case reports or perspective/opinion pieces (26, 57.8%), while studies presenting empirical findings were less common (11, 24.4%). Publications showed that academies were diversifying and increasingly were part of a broad range of organizations, including departments, hospitals, health science campuses, and national organizations. The mission, resources, and activities were similar across academies. Evaluation studies were largely limited to process measures, and rigorous studies examining outcomes (i.e., changes in academy participants) and impact on the organization at large were rare. Conclusions: The increase in the number of academy-related publications parallels the accelerating speed of the academy movement. To sustain this movement, rigorous studies must provide evidence that academies contribute to the revitalization of organizations' teaching mission and bring about an academic culture where educators thrive and where education is a legitimate career path.